Harlequin Ichthyosis: Case Series - Ezveci, Huriye; Dogru, Sukran; Akkus, Fatih; Gezginc, Kazim (Gynecology Obstetrics & Reproductive Medicine, 2024)
Objective: Harlequin ichthyosis (HI) is an autosomal-recessive inherited disorder. The incidence is extremely rare and is reported to range from 1/300 000 to 1/1 000 000. Some risk factors include preterm births and consanguinity. Prenatal DNA testing for the ABCA12 mutation aids in diagnosis. Although ultrasonography helps the diagnosis, the diagnostic value of a single ultrasound is low. It is fatal for the affected newborn after the first few days after birth, but few long-term survivals have been recorded. The hallmark of with disease is severely keratinized skin. This study aims to evaluate the prenatal and postnatal outcomes of cases with HI. Study Design: The study includes instances of HI that were diagnosed at the clinic throughout 2018–2023. The week of diagnosis, ultrasonographic findings, week of birth, and findings at the time of delivery for all patients were acquired via electronic reports and archival data. Data regarding the condition of viable fetuses was acquired using telephonic means. Results: The study included a total of five patients. There were prenatal ultrasonography findings in three cases. There were no prenatal ultrasound findings in the remaining two patients. Cordocentesis was applied to a single case using prenatal ultrasound diagnosis, and a normal genetic result was obtained. The remaining two cases refused to opt for the option of prenatal invasive testing. The termination option was not accepted in three cases with an intrauterine diagnosis. Prenatal ultrasonography revealed features showing skin thickening, ectropion, eclabion, oligohydramnios, and fetal growth restriction (FGR). Histological examination results of fetal skin biopsies in three cases showed consistent findings of epidermolytic HI, thus confirming the diagnosis of HI. The histological diagnosis of the remaining two patients was inconclusive. All cases are alive. Conclusion: It is advisable to conduct a methodical evaluation based on the clinical manifestations of the condition during the third trimester of gestation to diagnose HI, particularly in instances where there is no familial predisposition.